Ayollar yaktagi dizayn komponentlarini Valentina dasturi asosida raqamli loyihalash - Ochilov, Shokir Bakhtiyorovich; Abdullayeva, Gulsara Sevdiyorovna; Muminova, Gulandom Otabekovna (SCIENCE and SOCIETY, 2026)
This article discusses the process of designing the components of a women’s yaktak based on modern digital technologies. The main objective of the study is to create a women’s yaktak model that combines national and modern design using the Valentina and Gemini software programs. The research methodology includes design theory, digital modeling, and parametric construction methods. Initially, a visual sketch of the yaktak was developed using the Gemini program; subsequently, anthropometric body measurements were entered in the Tape section of the Valentina software, and patterns were constructed using the Pattern and Layout modules. As a result of the study, a technologically advanced digital pattern for a women’s yaktak was created, precisely matching the specified measurements. The findings demonstrate that the Valentina program offers advantages over traditional construction methods in terms of accuracy, flexibility, and time efficiency.
Keywords: Valentina software; Gemini software; digital design; women’s yaktak; design components; parametric construction; national design